Responding to sustainability: A model exploring the impacts of boards of directors and organisational strategic flexibility - Galbreath, Jeremy (Graduate School of Business, 2009)
As the strategic apex of decision making, boards of directors have ultimate responsibility in ensuring that firms address economic, environmental and social sustainability. We contend that board information-processing activities act as the mediational pathway by which board composition affects sustainability. Further, because of the complexity of the sustainability paradigm, strategic flexibility is posited to moderate relationships between information-processing activities and sustainable outcomes. The model proposed in this paper offers original insight into the drivers of sustainability in organisations and thus, we conclude the discussion with implications for both research and practice